Covid-19 pandemic and SMEs' performance in Latin America - Maikol Cerda; David Cervantes; Paul J. Gertler; Sean Higgins; Ana María Montoya; Eric Parrado; Carlos Serrano; Raimundo Undurraga; Patricia Ya\~nez-Pagans (Inter-American Development Bank (IDB), 2023)
The COVID-19 pandemic generated a large negative external shock to the global economy. Businesses worldwide were affected by economic, health, and mobility restrictions that impacted consumers' ability to access goods and services and firms' profitability and survival rates. In this paper, we study the economic performance of Latin American MSMEs during the pandemic using disaggregated and highfrequency administrative banking deposits and income data from Brazil, Chile, Colombia, Mexico, Paraguay, and Peru. We observe a sharp short-term decline in firm earnings due to the implementation of lockdowns during the second half of March 2020. We show this decline had a heterogeneous impact by economic sector, firm size, and transaction type (in-person vs. online). Focusing on financial technology adoption by studying the migration from in-person to online banking transactions, we find that MSMEs managed to recover revenues to pre-pandemic levels in early 2021 thanks to an increased share of online transactions and that industries facing higher physical exposure to the public (e.g., retailers) experienced a more considerable decline and a slower recovery.
Keywords: H81; I18; L25; O12; 330; Coronavirus; COVID-19; Latin America; Lockdowns; Smallbusinesses; Social distancing restrictions